Innovation in Urban Mobility as an Urban Solution towards More Sustainable Cities: The Case of Informal Urbanization - Elewa, Ahmed Khaled Ahmed (European Journal of Sustainable Development, 2018)
The main cities of emerging and developing countries (MCED) witness a growing economy accompanied by the continuous growth of its urban population and the chaotic urbanization, that is why the phenomenon of informal urbanization areas (IUA) is often associated with the MCED, IU areas generate a daily urban transport flows that contribute to multiple urban problems, mainly socio-economic issues, which impact the quality of urban life in negative way. The argument of the study refers to the possibility of achieving more sustainable cities through the using of innovation in UM (UM) as an urban solution. The study based on a theoretical study to define the intended meaning of innovation in UM, as well an empirical study through the analyzing of selected cases. The findings showed through lessons from practice that the using of innovative UM solutions is a sustainable upgrading approach that can contribute to achieve a better quality of urban life in the MCED with IU areas, also clarified the necessity to not to rely on this approach as a dominant approach but in integrated way with other traditional upgrading approaches, finally innovation in UM is not limited to the using of advanced and high tech solutions. Keywords: Innovation, Urban mobility, Sustainable cities, Informal urbanization